Does a standard myectomy exist for obstructive hypertrophic cardiomyopathy? From the Morrow variations to precision surgery. (15th January 2023) - Stefàno, Pierluigi; Argirò, Alessia; Bacchi, Beatrice; Iannone, Luisa; Bertini, Alenya; Zampieri, Mattia; Cerillo, Alfredo; Olivotto, Iacopo
Abstract: Objectives: The purpose of this work is to revisit the history of surgical treatment for obstructive hypertrophic cardiomyopathy (oHCM) over the last 60 years, in the light of advancing knowledge of the pathophysiology of obstruction. Methods: In this narrative review the contribution of the different surgical approaches to the field will be assessed in our personal experience in Florence. Results: Septal myectomy is the treatment of choice in patients with obstructive hypertrophic cardiomyopathy who remain symptomatic despite optimal medical treatment. Over the decades, numerous "theme variations" of the Morrow operation have been proposed, each of them targeting a specific pathophysiological determinant of left ventricular outflow tract obstruction. Conclusions: Precision surgery in oHCM patients today depends on the ability of the surgeon to combine and master these variations, with the bird's eye view allowed by climbing on the shoulders of giants. Graphical abstract: Unlabelled Image Highlights: Surgical myectomy is the treatment of choice for symptomatic patients with hypertrophic cardiomyopathy refractory to medical therapy. LVOTO has a complex pathophysiology to which both anatomical and functional anomalies concur. Multiple surgical approaches have been proposed to relieve LVOTO. The surgeon should combine and master these different techniques in order to offer a tailored approach.